Treatment strategy for late‐life depression - Hajime Baba (PCN Reports, 2023)
Abstract With the unprecedented aging of the world's population, the number of elderly patients with depression is expected to increase. However, management and treatment of late‐life depression (LLD) is more difficult than in early adults. Prior to treatment, diagnosis must take into account the differentiation from, and comorbidity with, organic brain diseases such as dementia and delirium, as well as depression caused by other physical diseases or medications. As clinical features of LLD, treatment response tends to be poor in older patients and recurrence rates are higher than those in early adult patients, therefore psycho‐social interventions on the basis of the patient's background and condition are important for LLD. The first‐line treatment strategy generally depends on the severity of the depression. Systematic psychotherapies, including cognitive behavioral therapy and problem‐solving therapy, have been reported to reduce depressive symptoms in LLD. Regarding pharmacotherapy, newer antidepressants are recommended for LLD, but careful attention to adverse events is required. Treatment using neuromodulation is also reported to be useful for LLD. In the current review, for further‐line treatment, treatment strategies were divided according to the level of first‐line treatment response. Evidence indicates that LLD is more heterogeneous than depression in younger adults, therefore when treating LLD patients it is necessary to take various conditions and situations into consideration, and to provide detailed treatment that is tailored to each patient.